2015
DOI: 10.1089/jpm.2014.0354
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Physical Restraint Use in Hospitalized Veterans at End of Life: An Analysis of Data from the BEACON Trial

Abstract: This is the first study to document that one in six hospitalized veterans were restrained at the time of death and to identify predictors of restraint use. Further research is needed to identify intervention opportunities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
3
8
0
Order By: Relevance
“… 7 , 12 This work extends other findings by reporting on physical restraint use, which is increasingly recognized as a burdensome intervention at the end of life. 35 In addition, although 2 previous small cohort studies reported high rates of antibiotic prescription among nursing home residents with advanced dementia at the end of life, the present study confirms these rates in a large population-based cohort. 18 , 44 …”
Section: Discussionsupporting
confidence: 82%
“… 7 , 12 This work extends other findings by reporting on physical restraint use, which is increasingly recognized as a burdensome intervention at the end of life. 35 In addition, although 2 previous small cohort studies reported high rates of antibiotic prescription among nursing home residents with advanced dementia at the end of life, the present study confirms these rates in a large population-based cohort. 18 , 44 …”
Section: Discussionsupporting
confidence: 82%
“…Factors that have been associated with the use of physical restraints in patients in ICUs were older age, MV use, and a low patient-to-nurse ratio [ 35 , 36 ]. Unfortunately, 16.3% of deceased patients had experienced physical restraints by the time of death, and approximately one out of four ICU patients died in restraints [ 37 ]. Our study may be the first to explore the utilization of inpatient physical restraints in the care of ICU COPD patients with and without cancer who received inpatient PC and also point out the difference between them.…”
Section: Discussionmentioning
confidence: 99%
“…While it is strongly recommended that no individuals including people with advanced dementia should be forcefed, tube feeding provides a safer way of administering foods and fluids to maintain the nutritional status of people categorised as having unsafe swallowing [14,90,91]. NG tube is rarely considered an option in people with late-stage dementia due to lack of cognition and intolerance [5,92]. Evidence also shows that PEG feeding is associated with a lower incidence of aspiration when compared with NG tube feeding [93].…”
Section: Perceived Benefits Of Tube Feeding In Advanced Dementia Indimentioning
confidence: 99%